(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
This study was designed to determine the canopy cover, c of the tropical forest and explore its effects on the interception loss amount. The study area was a reserved forest Lagong Hill Forest Reserve, Kepong, Selangor, Malaysia, where two plots with an area of 400 m2 (20 m x 20 m) each have been set up to collect the data. In order to determine the measured interception loss, rainfall, throughfall, and stemflow data have been measured on site. The tree with a diameter at breast height (dbh) of more than 10 cm was selected in collecting the stemflow data. Twenty-five (25) locations have been chosen for the digital hemispherical photographs to be taken. The forest standing of the study area has been visualised by Stand Visualization System (SVS) method, and WinSCanopy 2009a and RGBFisheye.exe application software has been used to obtain the canopy cover values. In this study, the correlation between canopy cover and interception loss were obtained for both plots. It is found that the Lagong Hill Forest Reserve varied has a compact canopy density with canopy cover up to 95%. This condition will affect the canopy interception loss value ranging from 24.83% up to 64.72%. The canopy cover and interception loss correlation denote that the interception loss amount reduces whilst the canopy cover increases.